Disaster and development - Collins, Andrew E. (Routledge, 2009)
This book provides accessible and up to date analyses of disasters and development linkages, addressing planning and response activities that accompany this field.
Includes bibliographical references and index
Keywords: Wirtschaftsentwicklung; Economic development; Natural disasters; Katastrophenmanagement; Naturkatastrophe